SISTERHOOD IN JODI PICOULT’S MY SISTER KEEPER - Pioro benevolent Lariesto; Hana Imelda Gultom (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This thesis paper, sisterhood in Jody Picoult’s My Sister Keeper. The Novel represents people especially women who shares honest thoughts, and feelings. The research itself is a library research because it solely focused on analyzing the novel with other relevant and supporting articles. This research also uses the mimetic approach proposed by Abrams. Which proposes that art is essentially an imitation of aspect of the universe.The analysis is focused on sisterhood, a central focus in feminism and in this case the feminist literary criticism. It can be explained as the sharing of experiences of oppression, and sharing the thoughts and feeling of honesty. The author writes Anna and Kate to represent people who experiences oppression. Anna losses her freedom as a person so she sues the court for freedom. In conclusion through her novel, the author portrays people who, through the process of forming a sisterhood, found solace from their suffering, gain understanding and achieve happiness.